Pengurusan Kurikulum Sekolah Menengah Dan Hubungannya Dengan Pencapaian Akademik - Rosnah, Selamat (1995)
The main purpose of the study was to investigate how systematic, effective and excellent is the curriculum management in the secondary schools today, to compare between the curriculum management in excellent achievement schools and the moderate schools and to find out whether curriculum management in school influence the Public Examination. Two sets of questionaire were used to identify the curriculum management system and the subject department management system. The respondents of the study are 32 Academic Secretaries and 253 Senoir Subject Teachers from 33 rural secondary schools in the District of Kuala Selangor, Sabak Bernam, Kuala Langat and Sepang, Selangor Darul Ehsan. The data was processed using SPSS For MS Windows 6.0 program. The main finding of the study was the curriculum management system including the management of each subject department in most of the secondary schools today is just satisfactory. Only a few schools was found to implement the systematic, effective and excellent curriculum management. It was also found that the curriculum management system in the excellent achievement schools is better than moderate ahievement schools and the effectivenese of the curriculum management system in the school is one of the factor that influenced the achievement of the school in the Public Examination. Based upon the findings, it is recommended that those involved in education especially in the curriculum and management department review the curriculum management system of their schools with the purpose of improving it.